KORELASI ANTARA KESIAPAN BELAJAR DENGAN HASIL BELAJAR SISWA DI SMA NEGERI 5 LAHAT - Deni Hartono (Geography Education Study Program, Universitas Samudra, 2021)
The aim of this study is to determine the correlation between the readiness to learn and result study of the students’on geography subjects in SMAN 5 Lahat. This research used descriptive quantitative method. The number of population is less than 100 people, in this study the sample is 63 students. The data collection techniques used documentation and questionnaires. The results of this study showed that the average score of student learning readiness of 79.66% on the criteria of being and the average student learning outcomes 82.86% on good criteria. Testing the hypothesis on the level of 95% or 0.05 indicates α r xy = 0.9133> 0.05 α rt n = 63 = 0.249 and thitung> ttable ie 34.12> 1.999 is means there is a positive relationship between learning readiness and students’ learning readiness and learning outcomes is 91.33% with high criteria. So, it means there is a significant corection between the learning readiness and the students’ learning outcomes at SMAN 5 Lahat. Keys words: Geography; Result Study; Kreadiness to learn